2002
DOI: 10.1046/j.1365-2036.16.s2.9.x
|View full text |Cite
|
Sign up to set email alerts
|

Wine stimulates gastric acid secretion in isolated rabbit gastric glands via two different pathways

Abstract: Background & aims: Alcoholic beverages such as beer and wine are well known to potently stimulate gastric acid secretion, most probably through an increase in circulating gastrin level. The present study examined whether or not wine stimulates gastric acid secretion by a direct effect on parietal cells, enterochromaffin‐like (ECL) cells or both. Methods: Gastric mucosa was isolated from female Japanese white rabbits and gland specimens were prepared by the collagenase digestion method. Acid secretion was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…reported that alcohol consumption significantly lowered treatment efficacy (70% among drinkers vs. 90% among nondrinkers, p = 0.004) [6]. The possible mechanism stems from the stimulation of histamine release, gastric acid secretion [22,23], and a change of intragastric microenvironment that influences the stability of antibiotics or enhances the growth of H. pylor i [24]. However, such differences were not seen in our study (presence vs. absence of alcohol consumption: 84.38% vs. 86.92%, p = 0.34).…”
Section: Discussioncontrasting
confidence: 66%
“…reported that alcohol consumption significantly lowered treatment efficacy (70% among drinkers vs. 90% among nondrinkers, p = 0.004) [6]. The possible mechanism stems from the stimulation of histamine release, gastric acid secretion [22,23], and a change of intragastric microenvironment that influences the stability of antibiotics or enhances the growth of H. pylor i [24]. However, such differences were not seen in our study (presence vs. absence of alcohol consumption: 84.38% vs. 86.92%, p = 0.34).…”
Section: Discussioncontrasting
confidence: 66%
“…In the past few decades, several studies have investigated the influence of alcoholic beverages on gastric acid secretion using intragastric titration in humans , as well as in animals, such as rats or dogs, or in isolated gastric glands from rabbits . To our knowledge, there have been only two studies comparing the effect of red wine and white wine on gastric acid secretion.…”
Section: Introductionmentioning
confidence: 99%
“…11 In the past few decades, several studies have investigated the influence of alcoholic beverages on gastric acid secretion using intragastric titration in humans 1 −3,12 as well as in animals, such as rats 13 or dogs, 14 or in isolated gastric glands from rabbits. 15 To our knowledge, there have been only two studies comparing the effect of red wine and white wine on gastric acid secretion. In a human intervention trial, Peterson and colleagues administered 300 mL of either red or white wine to healthy subjects and did not observe any difference in gastric acid secretion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For this reason, the delivery of antibiotics to the gastric mucosa is reduced. Other studies have reported that alcohol consumption also decreases the eradication success rate of PPI-based therapy (Hsu et al 2005) by stimulating gastric acid secretion (Tsukimi et al 2001;Matsuno et al 2002). In contrast, recent studies have reported that neither smoking nor alcohol consumption decreases the eradication success rate of vonoprazan-based first-line therapy (Sakurai et al 2017;Takara et al 2019), which can be explained by the more potent inhibition of acid excretion by vonoprazan than by PPI.…”
Section: Discussionmentioning
confidence: 96%